2014
DOI: 10.1016/j.carbon.2013.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative characterization of acidic groups on acid-treated multi-walled carbon nanotubes using 1-aminopyrene as a fluorescent probe

Abstract: Acidic functional groups produced on the surface of acid-treated multi-walled carbon nanotubes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…Finally, the mean surface acidity of centrifuged cMWCNT suspensions was calculated using Equation 3 to be 19.09 ± 0.52 mmol/g. We know of only one other work to quantify the acidic surface groups of carbon material in centrifuged cCNT suspensions;[49] in brief, using fluorescence spectroscopy and 1-aminopyrene dye-treated samples, it was determined that MWCNTs oxidized for 24 h with nitric and sulfuric acids were 15 – 22% oxidized, which is in accordance with the 23% level of oxidation calculated for our centrifuged cMWCNT suspensions.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Finally, the mean surface acidity of centrifuged cMWCNT suspensions was calculated using Equation 3 to be 19.09 ± 0.52 mmol/g. We know of only one other work to quantify the acidic surface groups of carbon material in centrifuged cCNT suspensions;[49] in brief, using fluorescence spectroscopy and 1-aminopyrene dye-treated samples, it was determined that MWCNTs oxidized for 24 h with nitric and sulfuric acids were 15 – 22% oxidized, which is in accordance with the 23% level of oxidation calculated for our centrifuged cMWCNT suspensions.…”
Section: Resultssupporting
confidence: 83%
“…[3739] While the Boehm method has been applied to the analysis of oxidized carbon materials for over fifty years,[3739,6369] a standard protocol has rarely been followed for the analyses of cCNTs. [24,29,32,35,36,43,49,50,52,54,55,7075] For example, there are different routines to determine endpoints, differences in base treatment times and agitation methods, differences in methods to address dissolved carbon dioxide, and differences in determining the mass of carbon material titrated. Herein, the first major parameter considered was the agitation method used to expose carbon materials to the chosen base – a process that can damage a carbon lattice and create new oxygen surface groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhou et al reported [9] nanodefects produced by a sulfonitric mixture at 373 K, as revealed by TEM observations, Raman spectroscopy and FTIR measurements. Nishikori et al [13] performed oxidation studies using an acidic mixture and employed XPS and the UV-vis absorption method using 1-aminopyrene as a fluorescent probe.…”
Section: Introductionmentioning
confidence: 99%
“…La Figura 6.6 muestra los difractogramas obtenidos. El pico de difracción a 26° (2θ) se refiere al plano (002) de la estructura hexagonal del grafito (Lu et al, 2008;Nishikiori et al, 2014;Rosca et al, 2005). Se observa que para las muestras T90, T110 y T130 este pico se aparta levemente hacia ángulos más bajos, indicando que la distancia entre las capas del grafito (capas del nanotubo) d002 se expande (de 3,42 a 3,45 Å) debido a la intercalación de iones sulfato y nitrato entre los cilindros coaxiales de grafeno que forman la estructura de los NTC (Li et al, 2016).…”
Section: Difracción De Rayos X (Drx)unclassified